The Impact of Differential Subsidence on The Integrity of Offshore Platform Jacket Using Linear Static Analysis - Suherman, Sarah (Universiti Teknologi PETRONAS, 2020)
Subsidence is the gradual caving in or sinking of an area of land. Subsidence is a major problem in civil engineering as it is considered as natural causes. When subsidence occurs to a certain extent, it can cause harm not only to the structure but to the surroundings as well. For this project we will identify how does an increment of subsidence impact Platform A jacket structure and how will it impact the global integrity of the structure. Many studies determine a platform's structural integrity by using methods such as pushover analysis based on the forces acting on the platform structure. To determine structural dynamic properties and responses, methods which uses linear static material behaviour are utilised. There are two approach that has been done when analysing subsidence for this project which are subsidence in the x and y-axis.